Commitment and change : Georges Sorel and the idea of revolution - Vernon, Richard, 1945- (University of Toronto Press, 1978)
This analysis of Georges Sorel's ideas on revolution and the original translations of some of his little-known writings on this theme offer a critical reassessment of Sorel's place in modern political thought.